Pertanggungjawaban Hukum Terhadap Tenaga Kerja Wanita Indonesia Yang Di Deportasi Berdasarkan Undang-Undang Nomor 39 Tahun 2005 - Wishnu Kurniawan; Erica Florentyna (Journal of Judicial Review, 2015)
This study aims to determine the causes of labor deported. In addition, this study also aims to describe efforts to protect migrant workers abroad.This research is a normative law. The subject of research is determined by purposive technique. With purposive technique chosen subject of study is one of PPTKIS Tanjungpinang and former migrant worker from East Java that the documents had been forged. Data were collected by interview. Examination of the validity of the data using a cross check, the cross-check between research subjects and the results of interviews with documents obtained during the study. The results showed that 1) The cause of the occurrence of falsification of former migrant worker’s document from East Java is due to a lack of understanding of migrant workers in the field of employment, especially procedures to work abroad, the document Prospective migrant workers has not been orderly for some residents in rural / remote, the appeal of promising economic in a foreign country, rampant Calo / sponsor of labor, thus deported 2) Implementing Private Placement of Indonesian Workers (PPTKIS) Tanjungpinang served as a supervisor, mentor, protector and is responsible for pre-placement, placement period, to the period after the placement of migrant workers.